Are there major developmentally regulated H4 gene classes in Xenopus? - Woodland, H R (1984)
Primer extension analysis has been used to study the principal H4 mRNAs present at different developmental stages and in several adult tissues of Xenopus borealis and X. laevis. In X. borealis a single sequence class predominates in oocytes, tadpoles and cultured fibroblasts. There is also a polymorphic minor type which shows no developmental regulation. The primer extension bands obtained from adult liver and kidney RNA appear to be the same as ovary and therefore these tissues almost certainly contain the same major H4 mRNA species. This is confirmed by S1 mapping of the 3' end of the mRNA. Thus for H4 genes in X. borealis there is no evidence of the kind of switches in histone gene expression seen in sea urchins or certain protostomes. The situation in X. laevis is complicated by considerably higher gene variability both within and between individuals. Nevertheless, in this species, as in X. borealis, there seems to be no major developmental switch in the regulation of H4 gene expression, a conclusion that also holds for an H1C and an H3 gene.